STUDY OF THE INFLUENCE OF LOADING RATE ON UNCONFINED COMPRESSIVE STRENGTH LIMESTONE SAMPLES AND SANDSTONE SAMPLES - FEBRIYAN TRINANDA (NIM : 12106022); Pembimbing : Dr. Ir. Suseno Kramadibrata M.Sc., YUDHA
One of the most commonly known test for rock mechanics is unconfined compressive strength (UCS) test. Unconfined compressive strength test is a test used to determine the strength of rock under one stress component (uniaxial) by using a compression Machine to push rock samples are cylindrical, beam, or a prism up to the rock sample failure . will provide mechanical rock properties described as unconfined compressive strength (σc), YoungÃ‚Â’s modulus (E), Poisson's ratio (υ), and stress Ã‚Â– strain curve. One of the factors that influence the results of unconfined compressive strength is loading rate . The purpose of this research is to study the effect of loading rate on the unconfined compressive strength of limestone samples and sandstone samples. In this research, 6 units of limestone samples and 6 units of sandstone samples are cylindrical were tested with unconfined compressive strength test at loading rate based on range from 100 kgf / min (+ 0.01 MPa /s) up to 600 kgf/min (+ 0:06 MPa / s). Based on the results of this research , and regression analysis for unconfined compressive strength test, the limestone samples in the test gave an effect relationship of increasing loading rate followed by increasing of unconfined compressive strength (σc ), but different with sandstone samples that did not give a definite influence of loading rate on unconfined compressive strength (σc). For Young's Modulus (E), Poisson ratio (υ) and stress - strain curves on limestone and sandstone samples were also not able to showed the influence of loading rate significantly.